Mosquitocidal efficacies of the medicinal plant senna alata Methanolic leaf extract against dengue and zika virus Vector aedes aegypti. - KARTHIYAYNI.N; PRAVIN. Y; PALANIKUMAR. M; MOHANRAJ. R. S; SUJATHA. P. S. (International Journal of Pharma and Bio Sciences, 2018)
Mosquito-borne diseases such as dengue, yellow fever, chikungunya and zika fever are among the leading causes of deaths world-wide. Aedes aegypti is a primary vector of dengue fever and There is no effective vaccine and treatment against dengue, chikungunya and zika fever; therefore the only way to reduce these diseases is mosquito control. The development of resistance in mosquitoes to most synthetic insecticides and repellents calls for the search for alternatives from plant origin. The present study explored the effects of Senna alata methanolic leaf extract on larvicidal, pupicidal, ovicidal and ovipositional deterrence against dengue and zika virus vector Ae. aegypti. Phytochemical and GC-MS analysis of the plant extract were carried out. Bioassay test was conducted for testing the efficacy of methanolic leaf extract of S. alata on Ae. aegypti at different stages of development. The effect of methanolic extract S. alata on the hatchability of Ae.aegypti eggs was determined. Hatching rate was calculated on the basis of non-hatchability of eggs. The effect of methanolic extract S. alata on oviposition of Ae. aegypti was determined under choice and no-choice oviposition test. Considerably low LC50 /24 hours values of methanolic leaf extract S.alata against different instar (I, II, III, IV and pupae) stages of Ae. aegypti obtained during the present study proved the larvicidal, pupicidal property of the plant. Young larvae were found to be relatively more susceptible than the older ones.The hatchability of Ae. aegypti eggs was decreased when placed in media of methanolic leaf extract. The reduction in percent hatch was inversely proportional to the concentration of methanolic leaf extract. Oviposition Active Index and Oviposition Deterrent Index indicated a low preference of Ae. aegypti to methanolic leaf extract treated medium for egg laying. In conclusion, this study recommends that the methanolic leaf extract of S.alata could be used as an alternative method in the Dengue and Zika virus vector management programs.